2012
DOI: 10.1155/2012/962101
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of EXPAREL ® (Bupivacaine Liposome Injectable Suspension) Administered by Peripheral Nerve Block in Rabbits and Dogs

Abstract: A sustained-release DepoFoam injection formulation of bupivacaine (EXPAREL, 15 mg/mL) is currently being investigated for postsurgical analgesia via peripheral nerve block (PNB). Single-dose toxicology studies of EXPAREL (9, 18, and 30 mg/kg), bupivacaine solution (Bsol, 9 mg/kg), and saline injected around the brachial plexus nerve bundle were performed in rabbits and dogs. The endpoints included clinical pathology, pharmacokinetics, and histopathology evaluation on Day 3 and Day 15 (2/sex/group/period). EXPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 25 publications
2
73
1
Order By: Relevance
“…The spill over injected steroids to systemic circulation causes weight gain, transient hyperglycemia, and bone loss, thus limit how many shots a patient can get in a year. Local anesthetic injection for terminal cancer pain, phantom limb pain, complex regional pain syndromes, etc, lasts hours to days typically, with the risk of life threatening overdose [3] [39]. STIDs of steroid or local anesthetics lasting week with minimal systemic blood concentration might greatly improve the treatment for those patients.…”
Section: Change the Benefit Vs Risk Profile Of Doxorubicin Other Chementioning
confidence: 99%
“…The spill over injected steroids to systemic circulation causes weight gain, transient hyperglycemia, and bone loss, thus limit how many shots a patient can get in a year. Local anesthetic injection for terminal cancer pain, phantom limb pain, complex regional pain syndromes, etc, lasts hours to days typically, with the risk of life threatening overdose [3] [39]. STIDs of steroid or local anesthetics lasting week with minimal systemic blood concentration might greatly improve the treatment for those patients.…”
Section: Change the Benefit Vs Risk Profile Of Doxorubicin Other Chementioning
confidence: 99%
“…Richard et al 78 , performed single-dose toxicology studies of 3 doses of Exparil (9,18, and 30mg/kg), and compared them to bupivacaine solution (9 mg/kg) and saline. When these were injected around the brachial plexus nerve bundle of rabbits and dogs, they found that at the same dose, Exparel resulted in a 4-fold lower maximum plasma concentration of bupivacaine and was well tolerated at all doses.…”
Section: Extended Peripheral Nerve Blocksmentioning
confidence: 99%
“…Exparel continues to be actively investigated for postsurgical analgesia via peripheral nerve block 78 and so far 2 phase 1 studies have been completed and, based on the safety data, the FDA has now approved subsequent phase 2 and 3 trials. If this, along with other newer analgesics continue to prove safe and efficacious, we may soon be able to provide long lasting pain relief to patients undergoing ambulatory hand procedures, without the use of oral medications and hence without their well described side-effects.…”
Section: Extended Peripheral Nerve Blocksmentioning
confidence: 99%
“…A very broad range of controlled release formulations have been developed to provide prolonged duration local anesthesia, including polymeric microspheres, [1][2][3][4][5][6][7] surgically implantable pellets, 8 microcrystals, 9 liposomes, [10][11][12][13][14][15] (including a formulation undergoing human clinical trials 16,17 ) lipospheres, 18 cross-linkable hyaluronic acid matrices, 19 lipidprotein-sugar particles, 20,21 cyclodextrin complexes, 22,23 liposomes loaded with cyclodextrin complexes 24 and implantable membrane matrices. 25,26 Such systems have extended the duration of nerve block to varying degrees ranging from hours to weeks, but have not been widely adopted clinically.…”
Section: Introductionmentioning
confidence: 99%
“…32,[38][39][40] Reporting of local tissue injury from local anesthetic controlled release formulations has been variable, in both animal and human studies. Most do not describe myotoxicity [2][3][4][5][7][8][9][11][12][13][14][15]18,[22][23][24] (including the liposomal formulation undergoing human trials 16,17 ), while some others document mild muscle injury comparable to single injections of unencapsulated drug. 10,25,26 In our own work, we have found muscle injury to be a ubiquitous finding in a wide range of extended-release bupivacaine formulations independent of the delivery vehicle 6,19,21,41 or co-encapsulated agent, 32,37,42,43 and it is sometimes severe.…”
Section: Introductionmentioning
confidence: 99%